Peran Good Corporate Governance Dalam Meningkatkan Corporate Sustainability Performance Perusahaan Keuangan Di Indonesia - Nia Sapitri; Yolandafitri Zulvia (Universitas Merdeka Madiun, 2026)
The purpose of this research is to investigate how Corporate sustainability performance (CSP) is impacted by good Corporate governance (GCG). The size and level of education of the top management team and board of commissioners serve as indicators of GCG. This analysis uses 50 samples from financial companies in Indonesia from 2017 to 2021. Using the SPSS 29 software, multiple regression analysis is the analytical method employed. This method is employed to observe the relationship between GCG and CSP. The study's conclusions indicate that board size significantly and positively affects the performance of economic, environmental, and social sustainability. In the meantime, the performance of economic, environmental, and social sustainability is adversely and significantly impacted by board education. Moreover, the size of the senior management team has little effect on environmental sustainability performance but has a negative and considerable impact on social and economic sustainability performance. On the other hand, the performance of economic, environmental, and social sustainability is adversely and significantly impacted by CEO education.